2015
DOI: 10.1515/intag-2015-0028
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Effects of Laser Irradiation on Maize Seeds

Abstract: A b s t r a c t. It is important to know the temperature changes in seeds that have been irradiated with laser light because this could have substantial practical and theoretical importance. Thus, the thermal effects of low intensity laser irradiation on seeds was studied, showing variation of temperature produced by laser light applied during 60 s on two maize seed genotypes, 'Toluqueño' and 'Cacahuazintle': crystalline and floury, respectively, under two different conditions: natural colour and dyed black, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 30 publications
0
11
0
1
Order By: Relevance
“…For this purpose, maize was selected as a model plant due to its significant economic value as a worldwide cultivated crop for its high starch content [31,32]. Furthermore, studies revealed that the laser is useful to improve the sanitary quality of maize seed [33]; this characteristic allows a seedling to have more strength to emerge from the soil [34].…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, maize was selected as a model plant due to its significant economic value as a worldwide cultivated crop for its high starch content [31,32]. Furthermore, studies revealed that the laser is useful to improve the sanitary quality of maize seed [33]; this characteristic allows a seedling to have more strength to emerge from the soil [34].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the diversity and potentiality of digital image processing techniques, in the present research, collections of thermal images in grayscale that are treated as a realization of random processes [1] are analyzed using the following statistical methods: histogram to obtain the gray levels distribution of images; the mean which is a measure of the image brightness; the variance that represents a measure of the image contrast, the entropy of both Shannon and Tsallis that indicate the average amount of self-information that contains the images and the probability density of the temperature variations for two genotypes of corn seeds: crystalline and floury in their natural state. The seeds were irradiated with laser light using a thermographic camera following the experiment described in [23], considering two exposure times: 15 and 35 s, with the aim of characterizing them quantitatively from the thermal images.…”
Section: Introductionmentioning
confidence: 99%
“…One of the PT techniques is the photoacoustic spectroscopy (PAS), used to study the optical and reflectance properties in different areas of knowledge, obtaining optical properties in biological materials, having relation to color, quality and state of degradation [9][10][11]. By using PT techniques, different crops such as wheat, acai, and corn seeds have been studied to obtain various optical and thermal properties [9,10,12,13]. These techniques may be used as a diagnostic, to obtain features of seeds.…”
Section: Introductionmentioning
confidence: 99%
“…These techniques may be used as a diagnostic, to obtain features of seeds. Likewise, analysis of thermal images [7,14] has shown that laser irradiation on biological object, such as corn, cause chemical reactions and temperature increment due to its chemical and physical characteristics [12,15,16]. So, it is important to know the temperature variations corn grains could experience.…”
Section: Introductionmentioning
confidence: 99%